Respon Pertumbuhan dan Produksi Kacang Ijo (Vigna radiata L.) Dengan Pemberian Dosis Pupuk Spry Up dan SP-36 - Wiji Subianto Muklisin, SP.; Ir. Junaidi, MP.; Ir. Supandji, MP. (Universitas Kadiri, 2021)
Mung bean (Vigna radiata L.) is one of the important food commodities in Indonesia, but its productivity is still low. One of the efforts to increase the productivity of mung beans is with balanced fertilization according to plant needs. The purpose of this study was to determine the interaction of dosage of spry up liquid fertilizer and SP-36 to produce the best growth and highest production. This research was a factorial experiment using a completely randomized design with two treatment factors and three replications. The first factor was the dose of liquid fertilizer spry up, with three levels, namely 1; 1.5; and 2 ml/plant. The second factor was fertilizer SP-36, with three levels, namely 5; 7; and 10 gr/plant. Observation data were analyzed with analysis of variance and continued with the LSD 5% if the results were significant. The results of the experiment showed that there was significant difference in the parameters of plant height, number of leaves, leaf area, and the amount of mung bean production at each increase in the treatment. The combination of treatment at the of liquid fertilizer spry up of 2 ml/plant and SP-36 10 gr/plant (S3P3) showed the largest yield, namely plant height 43.110 cm, the number of leaves 31 strands with a production of 97.985 gr/plant.Â Kacang hijau (Vigna radiata L.) merupakan salah satu komoditas pangan penting di Indonesia, namun produktivitasnya masih rendah. Salah satu usaha peningkatan produktivitas kacang hijau dengan pemupukan yang berimbang sesuai kebutuhan tanaman. Tujuan dari penelitian ini adalah mengetahui interaksi dosis pupuk cair spry up dan SP-36 untuk menghasilkan pertumbuhan terbaik dan produksi paling tinggi. Penelitian ini merupakan percobaan faktorial menggunakan Rancangan Acak Lengkap dengan dua faktor perlakuan dan tiga kali ulangan. Faktor pertama adalah dosis pupuk cair spry up dengan tiga taraf yaitu 1; 1.5; dan 2 ml/tanaman. Faktor kedua adalah pupuk SP-36 dengan tiga taraf yaitu 5; 7; dan 10 gr/tanaman. Data hasil pengamatan dianalisis dengan analisis varians dan dilanjutkan uji BNT 5% apabila hasil signifikan. Hasil percobaan menunjukkan bahwa terjadi interaksi yang berbeda nyata pada parameter tinggi tanaman, jumlah daun, luas daun dan jumlah produksi tanaman kacang hijau pada setiap kenaikan dosis perlakuan. Kombinasi perlakuan pada dosis pupuk cair spry up 2 ml/tanaman dan SP-36 10 gr/tanaman (S3P3) menunjukkan hasil terbesar yaitu tinggi tanaman 43,110 cm, jumlah daun 31 helai dengan produksi sebesar 97,985 gram/tanaman.